ROCK PHYSICS DIAGNOSTICS AND FORWARD MODELING STUDIES IN BOONSVILLE FIELD - PURNAMASARI, IDA AYU (2014)
The Boonsville Field is one of the largest gas fields in the US and it is located in the Fort Worth Basin, north central Texas. The reservoirs with the highest potential are found in the Bend Conglomerate which was deposited during the Pennsylvanian. The Bend Conglomerate was deposited in on fluvial-deltaic environment. It is subdivided into many genetic sequences which include depositions of sandy conglomerate which is the potential reservoir in the Boonsville Field. In this study, the reservoir characteristics of the Vineyard Formation are evaluated based on rock physics diagnostics ofthree wells drilled in the area.